Scaring the Hell Out of You: Scare-Tactics, Christian Horror Houses, and the Apocalypse of John - Stewart, Alexander E. 1979- (2017)
Western Christians are increasingly uncomfortable with the use of scare tactics in Christian proclamation and evangelism. An exception to this trend can be found in the seasonal theatrical production of Christian horror houses targeting youth in America. These productions are growing in popularity and they explicitly seek to produce fear in youth in order to motivate conversion. Practitioners of horror house scare-tactics claim support in the texts of Scripture, particularly the Apocalypse of John, for this rhetorical approach to evangelism. This paper will engage in interdisciplinary research in the social-sciences and biblical studies to explain why many critiques of the practice fail to persuade practitioners, and to note several points of critique which should result in evaluation and revision, if not abandonment, of the seasonal events.
Keywords: Revelation -- Apocalypse of John -- rhetoric -- fear appeals -- scare tactics -- Hell House -- horror houses -- Jonathan Edwards